Data Storage Energy Efficiency in the Zettabyte Era - Hormann, Peter; Campbell, Leith (Journal of Telecommunications and the Digital Economy, 2020)
Data storage has become an increasingly significant issue with the widespread availability of cheap storage technology and the development of global data centres for cloud storage. This paper reports a study of energy consumption for data storage in data centres. Unlike previous estimates, which have been extrapolations of broad energy usage within the data centre, we take a bottom-up approach. Firstly, we describe the technologies that can be used for data storage. Then we build up a model of energy consumption in data centres based on tiers of data storage. Based on published forecasts of data storage growth and assumptions about improving energy efficiency in technology and data centres, we then estimate the energy consumption for data storage in data centres in 2020. We show that energy consumption will rise substantially if a “business as usual” approach is adopted. We further show that the growth in energy consumption can be mitigated somewhat by adopting a more aggressive policy of data archiving on long-term, low-energy, “cold” storage; or more ideally purging data of little or no future value. This, however, would require a change in the popular assumption that data will be available readily online and forever.